1981
DOI: 10.1111/j.1365-3083.1981.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

β2‐Microglobulin‐containing IgG Complexes in Sera and Synovial Fluids of Rheumatoid Arthritis and Systemic Lupus Erythematosus Patients

Abstract: The occurrence and composition of complexed beta2-microglobulin (beta2m) in sera and synovial fluids of rheumatoid arthritis and systemic lupus erythematosus patients and control persons was investigated. Beta2m-containing complexes were detected in immune complex (IC)-enriched fractions isolated by precipitation with 3% polyethylene glycol 6000, in the macromolecular peaks after Sephadex G-200 gel filtration, and in IC desorbed from solid-phase Clq. Beta2m complexes were demonstrated also after precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…We proposed the evaluation of Sβ2M/SCysC as a possible predictor of SLE activity in lupus nephritis since previous studies had shown increased Sβ2M in patients with active SLE [11, 12, 13, 14, 15, 16, 17, 18]. It is of note that such previous findings could be influenced by GFR, so we included a GFR level adjustment, using the ratios Sβ2M/ SCysC and Sβ2M SCreat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We proposed the evaluation of Sβ2M/SCysC as a possible predictor of SLE activity in lupus nephritis since previous studies had shown increased Sβ2M in patients with active SLE [11, 12, 13, 14, 15, 16, 17, 18]. It is of note that such previous findings could be influenced by GFR, so we included a GFR level adjustment, using the ratios Sβ2M/ SCysC and Sβ2M SCreat.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of serum β2M (Sβ2M) were described in rheumatoid arthritis, Sjögren's syndrome and SLE. β2M is catabolized by the kidneys, and there is a linear inverse correlation between levels of Sβ2M and glomerular filtration rate (GFR); its elimination is constant in normal people when its production is also constant [15]. Approximately 99.5% of β2M is freely filtrated by glomeruli and reabsorbed in renal proximal tubules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) With respect to local enrichment it is of interest that higher Pint levels have been demonstrated in synovial fluids of patients with rheumatoid arthritis and SLE [28]. Fur thermore, P^m bears extensive homology to numerous molecules like the constant do main of immunoglobulin light chains, the T cell differentiation antigen, or the T cell anti gen receptor.…”
Section: Whymentioning
confidence: 99%